PEMBUATAN DASHBOARD PENJUALAN DAN PEMBELIAN HEVINDO SPORT - Christianto, Hizkia Aristyo; Trisnawarman, Dedi; Sutrisno, Tri (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Dashboards are used to present quality information on sales and purchases made available to managers or owners of a business. The purpose of this thesis is to assist shop owners in knowing the state of the sale and purchase of Hevindo Sport. Hevindo Sport is a shopping center engaged in sports, especially badminton. Dashboard uses the data warehouse Extract, Transform, and Load (ETL) method for the importing process. Importing ETL with the process of making dimension tables and fact tables. The dimensions of the table consist of the importing master table in SQL Server 2018. The fact table will be created after all dimension tables are finished and then create a dashboard. The results will be displayed in graphical form with the Tableau tools. The results of the dashboard are used to make decisions on the sale of goods reached in the safe zone and monitor the entry and exit of existing goods.